A novel test rig for the dynamic characterization of large size tilting pad journal bearings. (September 2016) - Forte, P; Ciulli, E; Saba, D
Abstract: The present work concerns the realization of a test bench for the dynamic characterization of high performance tilting pad journal bearings, within a collaboration between the Department of Civil and Industrial Engineering of Pisa, GE Oil&Gas and AM Testing. The objective is to cover journal diameters of interest of GE, from 150 to 300 mm, with peripheral speeds up to 150 m/s, static load up to 270 kN, dynamic loads up to 30 kN and frequencies up to 350 Hz, performances that make the apparatus very competitive worldwide. The adopted configuration has the test article (TA) floating at the mid-span of a rotor supported by two rolling bearings. The TA is statically loaded by a hydraulic actuator and excited dynamically by two orthogonal hydraulic actuators. Construction was recently concluded and preliminary tests are under way. In order to assess in advance the possible accuracy of the tests, a dynamic lumped parameter model of the test bench was developed to perform virtual experiments, including several possible sources of experimental errors and uncertainties. The model was implemented using reduced stiffness and mass matrices obtained from Finite Element Analysis by Component Modal Synthesis.